Understanding factors affecting breastfeeding practices in one city in the Kingdom of Saudi Arabia: an interpretative phenomenological study - Murad, Amal (Int Breastfeed J, 2021)
BACKGROUND: Breastfeeding duration has declined in the Kingdom of Saudi Arabia (KSA) in recent decades, although accurate national data about different breastfeeding indicators by infant age are lacking. This qualitative study, the first in KSA, aimed to understand the factors affecting mothers’ decisions and experiences regarding any breastfeeding practices. METHODS: A qualitative phenomenological approach was used to investigate mothers’ experiences of breastfeeding. Non-probability convenience sampling and snowballing strategies were designed to recruit participants. Semi-structured interviews were conducted with 16 mothers, from two hospitals and three primary health clinics in Al-Madinah city, from December 2017 to March 2018. Interpretative phenomenological analysis was the analysis framework. RESULTS: Three themes were identified: 1) ‘Up against the system’: policies, staff and systems were the main barriers to exclusive breastfeeding; 2) ‘Social support and negativity’: family support in the first 40 postpartum days protected breastfeeding continuation and was highly appreciated, but negative comments limited breastfeeding practices thereafter; and 3) ‘Managing tensions’: mothers’ religious beliefs about breastfeeding boosted their decisions; however, the challenge of managing tensions influenced mothers to stop breastfeeding earlier than they wished. The study revealed that mothers had no doubts about wanting to breastfeed their babies; but continuation was adversely affected by unhelpful hospital policies and staff actions, the lack of ongoing social support, and by others people’s negativity, rather than by the mothers’ own views. Stopping breastfeeding earlier than planned was a complex decision for most mothers. However, mothers said that they intended to breastfeed their next baby successfully. CONCLUSIONS: Healthcare professionals (maternity staff, paediatricians and pharmacists) need education and training to support exclusive breastfeeding effectively. Increasing the number of hospitals with Baby Friendly Hospital Initiative accreditation, which includes staff practice changes, is needed to protect and support exclusive breastfeeding. Ongoing professional and peer support, and improving conditions at workplaces and universities, are needed to help mothers to continue breastfeeding successfully. Effective, coordinated national policies can support mothers’ decisions in relation to breastfeeding. Such changes will reduce the tensions experienced by women and help them to achieve their breastfeeding goals and to breastfeed for longer.